Precursors for PbTe, PbSe, SnTe, and SnSe synthesized using diphenyl dichalcogenides. Issue 65 (27th July 2018) - Wang, Zhongyong; Ma, Yuanyu; Vartak, Prathamesh B.; Wang, Robert Y.
Abstract : Alternative metal chalcogenide precursor syntheses (instead of hydrazine or thiol–amine approaches) along with corresponding thermoelectric properties of PbSe x Te1− x films. Abstract : We create precursors for PbTe, PbSe, SnTe, and SnSe by reacting Pb or Sn with diphenyl dichalcogenides in a variety of different solvents. We then deposit PbSe x Te1− x thin films using these precursors and measure their thermoelectric properties. Introducing Na-dopants into the films allows the thermoelectric properties to be varied.